DOES GENDER MAKE A DIFFERENCE IN PROBLEM BEHAVIORS? - Ahmad Badayai, Abdul Rahman (International Journal of Psychosocial Rehabilitation, 2020)
Gender differences exist in prevalence, developmental course, and factors and also processes that contribute to the development of problem behaviors. The most apparent aspect of gender differences in the way that problem behaviors expressed in boys and girls could be seen in delinquent behaviors. However, much of the research sampling on problem behaviors have been based on male samples. Thus can influence estimates of the prevalence of problem behaviors and how it is defined. For instance, it is commonly reported that male adolescents exhibit significantly higher levels of aggression than do female adolescents. Therefore, the research is aimed to study gender differences in protective factors, executive dysfunction, and symptoms of problem behaviors. The study consisted of 404 respondents of different problem behaviors such as gang fights, homicide, out of control behaviors, rape, armed robbery, drug trafficking, and drug use. Developmental Assets Questionnaire-Malaysian Version (DAQ-MV), Behavior Rating Inventory of Executive Function- Self Report (BRIEF-SR), and Achenbach System of Empirical Behavior Assessment- Youth Self-Report (ASEBA-YSR) were employed in the study. The results based on the T-testanalysis showed that there were gender differences in protective factors, executive dysfunction, and symptoms of problem behaviors. An advanced study is required in determining contributing factors of gender difference in problem behaviors. Moreover, the study contributed to the theoretical foundation and psychological study in the study of forensic and criminal psychology and at-risk children.